The new materiality: digital dialogues at the boundaries of contemporary craft - Wilson, Fo (Cultura Visual, 2011)
The title of my paper takes its name from a travelling exhibition I have curated, which is currently showing at the Fuller Craft Museum just outside of Boston, Massachusetts in the United States through February of next year. The exhibition, The New Materiality: Digital Dialogues at the Boundaries of Contemporary Craft, examines the work of sixteen established and emerging makers working within traditional craft disciplines or with traditional craft materials that are treading compelling territory between their mediums and emergent technologies. They are by no means alone and are but a sampling of practitioners in America that are bypassing the restraints of their given disciplines, forging new ground and ignoring conventional means of categorization. These makers are embracing technologies that are increasingly ubiquitous in the culture-at-large, and using them as new materials in their work. In addition, their work shows us how the lines between art, craft, and design, are becoming more porous as each area co-opts various theoretical, technical and philosophical aspects of the other, thus asking us to scrutinize the distance between them in contemporary creative work.